The radical element 12 stories of daredevils, debutantes, and other dauntless girls - Spotswood, Jessica; Adler, Dahlia; Lee, Mackenzi; Bowman, Erin; Shepherd, Megan; Spotswood, Jessica; McLemore, Anna-Marie; Nijkamp, Marieke; Clayton, Dhonielle; Tash, Sarvenaz; Lee, Stacey; Medina, Meg; et al. (Candlewick Press, 2018)
An anthology of historical short stories features a diverse array of girls standing up for themselves and their beliefs, forging their own paths while resisting society's expectations
Keywords: Selbstverwirklichung; Amerikanisches Englisch; Erzählung; Frauenemanzipation; Historical fiction, American; Short stories, American; Self-realization / Fiction; Historical fiction; Short stories; YOUNG ADULT FICTION / Girls & Women; YOUNG ADULT FICTION / Historical / United States; YOUNG ADULT FICTION / Short Stories; YOUNG ADULT FICTION / Historical / United States / General; Anthologie